Essays in development macroeconomics - Salles, João Moreira (2012)
Developing macroeconomics is less about looking for ways to say that economic rules stemming from research in developed countries don\'t apply to emerging-markets, than it is about trying to understand the many stages these economies go through in the natural course of their development. There are, of course, exceptions, but economic phenomena tend to have common sources. These are, after all, generated by the incentives, designed or natural, that people face when dealing with their day to day decisions as they go about their everyday lives. In the two essays that follow, we try to stay true to that fundamental belief. Instead of searching for the proverbial \"jabuticaba\", we strive to understand how countries in different stages of development deal with a fundamental feature of \"growing pains\": crises, be they imported or locally generated. In the first essay, we look at an entirely novel feature of (some) developing economies: the potential to implement certain countercyclical policies when faced with an external shock. During the financial crisis of 2007-2009, to respond to a sudden stop in capital flows, many central banks in emerging market economies relied on credit policies. We build a quantitative small open economy model to study these credit policies. The main innovation of our setup is the presence of two imperfect credit markets, one domestic and the other international, and of two types of firms. The exporter is assumed to have access to both credit markets, while the wholesale firm can only borrow in the domestic market. During a sudden stop, exporters, faced with higher spreads for international credit lines, repay part of their foreign debt, tap the local market for funds and cause spreads to increase in the domestic market. This increases financing costs for all firms, causes a deterioration of the balance of payments and depresses output. Calibrating the model to match Brazilian data, we assess the effects of two policies implemented by the Central Bank of Brazil: (i) lending to exporters using previously accumulated foreign-exchange reserves and (ii) expanding credit in order to reduce spreads in the domestic market. The model suggests that both policies probably raised GDP, but that the latter may well have decreased welfare. Moreover, had the central bank not been able to use foreign reserves as the source of funding, lending to exporters would also have reduced welfare. In the second essay, we look at less promising situations, when countries are faced with default. In this work, we take a broader view, noticing that some of the salient features of the theoretical literature on sovereign debt, including its prediction that almost all defaults should arise in \"Bad Times\", are at odds with the data: over 38% of defaults actually occur in \"Good Times\", as measured by an HP filter. We explore the specific characteristics of both types of default. We first review some definitions of good and bad times, revealing that the resulting classification can differ greatly and have important implications for the overall analysis. Then, we present econometric evidence that failures to repay foreign debt in good times can, usually, be rationalized by three components: (i) changes in the political environment, (ii) hikes in global interest rates and (iii) instances in which good HP times actually take place under quite poor economic conditions. Finally, we present some suggestive indications that the duration of the episodes varies substantially with the type of default that precedes them as well as with the environment in which they occur, drawing some important implications for the understanding of economies\' post-default market access.